The Influence of Advergaming over university students in Lima - Garrido Gallardo, Alice (2014)
In times where the consumer is able to find what he wants without being interrupted by advertising, advertisers are required to expand their messages through new alternatives that connect the audience with the brand in an attractive way. The advergame is part of these new tools as it seeks to retain consumers through interactive games that represent the brand’s values, characteristics and benefits. To understand the influence of this advertising tool in Lima’s youth, this article makes an analysis on the attitude they generate towards the brand depending on the treatment that is given in the game, the exposure time and other variables.